Keunikan Yesus Kristus Sebagai Imam dan Implementasinya bagi Penginjilan Dunia - Ruseniati (Jurnal Missio Cristo, 2021)
Abstract: The phrase "Christ as Prophet, priest and King" is familiar to our ears, perhaps even deep in the minds of every believer. Of course, our belief in the three roles of Christ is a divine function that allows God's word to be conveyed to the world, the substitution and redemption of human sin, and God's absolute rule. That means that the office of Christ as a Prophet, Priest, and King does not stop at Jesus alone, but has implications for ourselves as His people. In this paper, the topic discussed is about Jesus Christ as a true Priest. Why? not to neglect or separate the other two offices of Christ. but as an effort to explore the meaning of the office of Christ as a priest. Because there are still "Christians" who do not clearly understand the meaning of the three offices of Christ for the practice of world evangelism. Then how does this doctrine of Christology, which seems so transcendent, relate to the practical life of humans every day? How should this concept shape the practice of world evangelism? So it would be nice to discuss three office that are focused on each position. As in the Old Testament the role of Mediation of prophets, priests, and kings is filled with separate individuals, the three offices are now united in one person Jesus Christ. This truth must be clarified to believers so that they understand the implementation of world evangelism.